Analysis Of Kutacane Substance Earning System - Muliadi Sirait; Adi Sastra Tarigan; Siti Anisah (INFOKUM, 2021)
One of the security systems at the substation is grounding. The grounding system is a conductor system that connects the system, equipment body and installation with the earth/ground so that it can protect humans from electric shock, as well as secure in-stallation components from the danger of abnormal voltage/current. The results of the measurement analysis using an earth tester on the Kutacane substation equipment, all observations show the grounding resistance is in a safe condition with the overall re-sults showing a smaller number below 1ohm. And provide a safe impact on the distri-bution system from voltage surges and lightning surges and provide a safe impact on humans from induced voltages.